Job Satisfaction and Marital Adjustment among Paramedical: Mediating Role of Work Family Conflict - Iram Batool; Shaukat Hussain; Ruqia Safdar Bajwa (Journal of Business and Social Review in Emerging Economies, 2017)
Purpose: An extensive pressure arose by work environment or by family environment resulted as work-family conflict. Occurrences of such conflicts are observed when employees experienced interference of work to family and family to work. Keeping the literature available on effects of work-family conflict in relationship to job satisfaction and marital adjustment, this study was designed to investigate the mediating role played by work family conflict between the relationship of job satisfaction and marital adjustment among paramedical staff. Another aim of this study was to explore the relationship among three variables. Furthermore, it was aimed to find out if there are any differences on gender or other demographical variables.  A sample of 100 employees was taken from Jhang and Faisalabad city. Instruments for measuring Work family developed by Netemeyer et al. (1996), job satisfaction developed by Paul E. Spector, (1994), and adapted and translated by Shazad, (2011) were used. Dyadic adjustment scale developed by Spanier, (1976) and adapted and translated into Urdu by Naseer (2000) were also used. Results revealed positive correlation between work to family and family to work conflict, while negative with marital adjustment and job satisfaction. The regression analysis showed Job satisfaction contributed 29% and family to work contributed 27% in predicting marital adjustment. Significant gender differences were found. The results of partial least square structural equation modeling (PLS-SEM) found significant mediating role of work to family conflict and family to work conflict.